Pharmacological and non-pharmacological modulation of endoplasmic reticulum stress in pediatric diabetes - Giannakopoulos, Aristeidis P. (Frontiers in Endocrinology, 2025)
In all forms of pediatric diabetes, the endoplasmic reticulum (ER) stress acquires a significant role, as a factor that contributes to the dysfunction and apoptosis of the pancreatic β- cells. The integrity of the ER response is critical as a molecular mechanism for alleviating stress during insulin biosynthesis and processing, regardless of the diabetes subtype. While achieving euglycemia remains central to diabetes management, there is growing recognition that targeting ER stress presents a promising therapeutic strategy, given that accumulating evidence shows that ER stress acts not only as a consequence but also as a key contributor to diabetes pathogenesis. This review explores the mechanisms of ER stress across all forms of diabetes, discusses both pharmacological and non-pharmacological approaches to modulating ER stress—with particular attention to medications that are already approved for use in children, such as metformin —and examines the potential of combining ER stress modulation with insulin therapy in order to optimize the metabolic homeostasis for the β-cell function and survival.